Community-Centric Approach: Bhabinkamtibmas Strategies in Mitigating COVID-19 Transmission Within the Cultural Landscape of Hukurila - Sudartomo, Nono; Pariela, Tonny Donald; Pelupessy, Pieter Jacob (Baileo: Jurnal Sosial Humaniora, 2024)
This study explores the strategic role of Bhabinkamtibmas—a community-based police officer—in mitigating the transmission of COVID-19 within the cultural setting of Hukurila, Maluku. Unlike general law enforcement roles, Bhabinkamtibmas acts as a bridge between state health policies and community practice. Using a qualitative approach through in-depth interviews, observations, and document analysis, this research uncovers how Bhabinkamtibmas actively promotes health education, distributes masks, and supports vaccination campaigns. Their role extends into the implementation of the 3T (Testing, Tracing, Treatment), establishing health centers, organizing color-coded zoning, and initiating local COVID-19 task forces. Collaborating with Babinsa, Bhabinkamtibmas ensures community compliance with health protocols and facilitates quarantine and emergency responses. The findings underscore a community-centric model that integrates cultural sensitivity with institutional synergy. This article contributes new insight into the adaptive role of Bhabinkamtibmas in public health crises and offers recommendations for strengthening community-based health governance in similar cultural contexts.